The effect of group discussion teaching on students' reasoning ability in solving physics problems - G. Ahmady; M. Saberi; F. Ahmadi (Fanāvarī-i āmūzish, 2020)
Background and Objectives: Education in today's world has a different meaning from the past, so there should be changes in the attitude and teaching method of teachers. Nowadays, teaching basic sciences is of special importance, and this issue requires teachers to be taught new teaching methods that make them learn these subjects better, including physics. Numerous studies have shown that increasing scientific reasoning leads to success in learning content knowledge. So, instead of considering several physics training courses to learn content knowledge, special teaching methods such as reasoning can be created in students with new teaching methods so that they can learn more spontaneously and keep pace with the development of science and technology. Formation. The relationship between teaching methods and the development of scientific reasoning has been extensively studied and it has been shown that the active teaching method enhances the abilities of scientific reasoning. Group discussion teaching is one of the methods of inclusive education that uses this method; learners actively participate in discussions and give them the opportunity to share their opinions and experiences with others. This article examines the effect of discourse-based education through group discussions on students' ability to reason scientifically in physics. Methods: This research is a quasi-experimental pre-test-post-test with a control group. The statistical population is all 10th grade female students of the second year of high school in Isfahan in the 2017-2018 academic years. The sample of this research was selected by multi-stage cluster sampling method. Measurement tool, a test to assess students' ability to reason scientifically in physics as a researcher-made with a reliability of / 76. Using the opinion of experienced professors in the field of physics education, its questions were content narrated. Each question was designed as four options and students were asked to write their reason in a descriptive way to select the desired option to further examine their type of argument. To score, Miyazaki (2000) model is used, which includes four different levels of reasoning in mathematics. In this study, the total score of each student is considered as the level of his physical reasoning ability. Since the answers to the questions were asked descriptively, to reduce the effect of the teacher's judgment, Cronbach's alpha was used for the correctors, which was 0.82. Findings: In the descriptive statistics section, the studied variables were analyzed using statistical index tables, mean and standard deviation, and in the inferential statistics section, the research hypotheses were analyzed using analysis of covariance and Pearson correlation coefficient. The results showed that the ability of physical reasoning and inferential reasoning of students in the experimental group is higher than the control group, but teaching through group discussions did not change much in the level of inductive reasoning of students. Conclusion: According to the research findings, there is a significant and inverse relationship between the ability of both deductive reasoning and inductive reasoning in both groups of testing and evidence, meaning that by increasing the ability of inductive reasoning, students use less inductive reasoning to answer questions. Therefore, teaching through group discussion has been able to have a positive effect on students' reasoning ability in answering physics questions.